Front Cover: Druggability Assessment for Selected Serine Proteases in a Pharmaceutical Industry Setting (ChemMedChem 21/2020). (22nd October 2020) - Wehrhan, Leon; Hillisch, Alexander; Mundt, Stefan; Tersteegen, Adrian; Meier, Katharina
Abstract : The Front Cover shows the backbone representation of a protein structural ensemble for the serine protease FXa with a reticle pointing at it. The potential of targeting a protein with a drug‐like molecule plays an important role in early drug discovery. In their study, the authors address the topic of target druggability assessment. They present key insights from high‐throughput screening (HTS) and protein structure‐based druggability assessments and illustrate that conformational variability matters. More information can be found in the Full Paper by Leon Wehrhan, Katharina Meier et al.